Dampak Perubahan Work From Home Terhadap Motivasi Kinerja Karyawan Dimasa Pandemi Covid-19 - Silvi Tri Wardani; Nuri Aslami (Universitas Labuhanbatu, 2022)
The world, including Indonesia, is being hit by Corona Virus Disease (Covid-19). Even though direct labor is often carried out in schools, the effects of Corona Virus Disease (Covid-19) are felt in the workplace. Work has to be done remotely or online during the coronavirus epidemic, which is often known as